Person-centered care: preferences and predictors in speech-language pathology and audiology practitioners - Mahomed-Asmail, Faheema; Hlayisi, Vera-Genevey; Joubert, Karin; Metcalfe, Louise Anne; Graham, Marien Alet; Swanepoel, De Wet (Frontiers in Psychology, 2023)
Introduction Increasingly person-centered care (PCC) is being recognized as an important aspect of speech-language pathology and audiology (SLP/A) service delivery. This study aimed to (i) identify preferences toward PCC; (ii) determine predictors of these preferences; and (iii) describe the understanding and views of PCC among SLP/A in South Africa. Methods A mixed-method design was followed utilizing an online survey and four focus group discussions. The survey included demographic questions, the modified Patient-Practitioner Orientation Scale (mPPOS), the Ten-Item-Personality-Inventory (TIPI) and an open-ended question. The focus group discussions included prompting questions which facilitated an open-ended discussion. Results A total of 91 practitioners (39.6% speech-language pathologists) completed the online survey, with nine (44.4% audiologists) participating in the focus group discussions. A high preference toward PCC was noted, with a total mean mPPOS score of 4.6 (0.6 SD). Quantile regression analysis revealed four predictors (age, home language, sector, and personality trait openness) associated with PCC preferences. Three main categories emerged from the open-ended question and focus group discussions: (i) Positive experiences with PCC; (ii) restrictions toward PCC, and (iii) PCC exposure. Discussion Positive (age and personality trait openness) and negative (home language and sector of employment) predictors toward PCC exist among speech-language pathologists and audiologists, with an overall general preference toward PCC. Practitioners experience facilitators and barriers toward implementing PCC including the extent of personal experiences, available resources and tools as well as workplace culture. These aspects require further investigation.